2018
DOI: 10.1021/acschemneuro.8b00002
|View full text |Cite
|
Sign up to set email alerts
|

Single Site Fluorination of the GM4 Ganglioside Epitope Upregulates Oligodendrocyte Differentiation

Abstract: Relapsing multiple sclerosis is synonymous with demyelination, and thus, suppressing and or reversing this process is of paramount clinical significance. While insulating myelin sheath has a large lipid composition (ca. 70-80%), it also has a characteristically large composition of the sialosylgalactosylceramide gangliosde GM present. In this study, the effect of the carbohydrate epitope on oligodendrocyte differentiation is determined. While the native epitope had no impact on oligodendroglial cell viability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Exogenous administration of GM4 or GD1a induces oligodendrocytes proliferation and differentiation (Qin et al, 2017;Kieser et al, 2018), a process that is important for remyelination and is impaired in MS (Franklin and Ffrench-Constant, 2008). One of the reasons for limited remyelination in MS is the persistent presence of aggregates of the extracellular matrix protein fibronectin in MS lesions, resulting in inhibition of oligodendrocyte progenitor cell (OPC) maturation and differentiation (Stoffels et al, 2013).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Exogenous administration of GM4 or GD1a induces oligodendrocytes proliferation and differentiation (Qin et al, 2017;Kieser et al, 2018), a process that is important for remyelination and is impaired in MS (Franklin and Ffrench-Constant, 2008). One of the reasons for limited remyelination in MS is the persistent presence of aggregates of the extracellular matrix protein fibronectin in MS lesions, resulting in inhibition of oligodendrocyte progenitor cell (OPC) maturation and differentiation (Stoffels et al, 2013).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Interestingly, one study on fluorinated GM4 derivatives reported a significant change in biological effects between fluorinated and non-fluorinated analogues [113]. GM4 is a sialosylgalactosylceramide ganglioside which is a major constituent of myelin sheath.…”
Section: Replacement Of Oh Functional Groupsmentioning
confidence: 99%
“…The diversity of mammalian and bacterial “ glycospace ” provides a rich platform from which to design tailored glycomimetics for applications in medicine Through relatively modest structural modifications, the natural role of complex carbohydrates in molecular recognition events can be harnessed for therapeutic purposes . Subtle, often single site, alterations are sufficient to markedly enhance a biological response or even to engage pathways that elude the native sugars . Of the plethora of structural modifications employed in glycomimic design, formation of C ‐glycosides is arguably one of the most common (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…A second strategy in devising metabolically robust glycomimics is the strategic OH → F substitution at C2 of pyranoside glycosyl donors . This seemingly subtle modification introduces several notable features that include enhanced hydrolytic stability, retention of the electronegativity intrinsic to the native structure, and the ability to direct glycosylation selectivity , , , . A classic bioisostere of the hydroxyl group, fluorine also functions as a valuable 19 F NMR probe (Figure , upper) and allows various physicochemical parameters to be modulated such as lipophilicity, metabolic stability, and the p K a values of neighbouring groups .…”
Section: Introductionmentioning
confidence: 99%